Delitos Informáticos - Villavicencio Terreros, Felipe A. (2014)
In recent times, due to the development of information technology,a new form of crime called informational crimes has developed. in relation to this new type of crime, a special criminal law was issued, whose purpose is to prevent and punish illegal activities that affect computer systems and datas, secret communications, and other legal goods that are affected withthis type of crime, such as equity, public faith and sexual freedom.